Implementasi Video Misi dan Visi Sekolah Dasar Charitas Batam - Inocenth ramdhany; Syaeful Anas Aklani; Zulkarnain Zulkarnain (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2025)
This community service project aims to assist SD Charitas Batam in visualizing the school’s vision and mission through an informative and engaging video. Currently, the delivery of the school's core values is still limited to print and verbal media, which are less effective in terms of appeal and reach. This project involved planning, filming, editing, and finalizing the video using a professional multimedia approach. The final output, consisting of a 2–5 minute main video and several short versions, was delivered to the school for use as promotional and digital documentation materials. This initiative is expected to enhance the school’s image and strengthen communication of its institutional values to the wider community.